1992
DOI: 10.1021/bi00145a002
|View full text |Cite
|
Sign up to set email alerts
|

Minimum length of a sequence-specific DNA binding peptide

Abstract: NMR experiments show that a stable complex can be formed between a 14-base-pair oligonucleotide and a disulfide-bonded dimer of a peptide containing 27 residues of the basic region of the yeast transcriptional activator GCN4; the complex is in slow exchange on the NMR time scale. In contrast, a nonspecific complex is in fast exchange on the NMR time scale. DNase I footprinting experiments show that dimers of peptides containing as few as 20 residues of GCN4 bind DNA with sequence specificity similar to that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
80
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 27 publications
5
80
1
1
Order By: Relevance
“…Particularly relevant are those based on dimeric bZIP basic regions, in which the natural C/C-terminal leucine zipper is replaced by artificial dimerizers [14][15][16][17] . Some of these designs have gone even further and incorporate switchable elements that allow conditional off/on DNA binding by the application of external stimuli such as light or metal ions [18][19][20][21][22] .…”
mentioning
confidence: 99%
“…Particularly relevant are those based on dimeric bZIP basic regions, in which the natural C/C-terminal leucine zipper is replaced by artificial dimerizers [14][15][16][17] . Some of these designs have gone even further and incorporate switchable elements that allow conditional off/on DNA binding by the application of external stimuli such as light or metal ions [18][19][20][21][22] .…”
mentioning
confidence: 99%
“…[11][12][13][14][15] For example, a study by Kim and co-workers, compared a library of peptide dimers (of different lengths) derived from the basic domain of the GCN4 transcription factor. These peptides all bore a GGC motif toward the C terminus to allow dimerisation through thiol oxidation.…”
Section: Dna Binding Peptide Sequence Designmentioning
confidence: 99%
“…Both DNase I footprinting and circular dichroism (CD) melting experiments revealed that the 15 amino acid sequence KRARNTEAARRSRAR contains the necessary conserved residues required for the formation of specific contacts with the DNA target site CRE, whereas binding to AP1 required additional conserved residues. [13] The linker region LQRMKQL, separating the basic and leucine zipper domains and which allows for the formation of an uninterrupted a-helix, [36] has been reported to be important for thermal stability on binding to both CRE and AP1 DNA. [11,13] Based on this literature our initial design, Ac-ALKRARN-TEAARRSRARKLQRMKQLGGCG-NH 2 , included both the basic domain and the flexible linker region so as to achieve strong and selective DNA binding.…”
Section: Dna Binding Peptide Sequence Designmentioning
confidence: 99%
See 2 more Smart Citations